Reply: The new ERS/ATS standards on lung function test interpretation: some extant limitations. Issue 2 (11th August 2022) - Stanojevic, Sanja; Kaminsky, David A.; Miller, Martin; Thompson, Bruce
We would like to thank J.A. Neder for his thoughtful correspondence and critical review of the updated ERS/ATS technical statement on pulmonary function test interpretation [1]. As the updated technical document focuses on physiological interpretation of pulmonary function tests, we welcome the discussion on how to incorporate these updated standards into clinical practice. The updated technical statement on pulmonary function test interpretation focuses on physiological interpretation. There are important considerations regarding how these updated standards can be incorporated into clinical practice. https://bit.ly/3xDZGOJ